The idea of commercial society in the Scottish enlightenment - Berry, Christopher J. (Edinburgh University Press, 2013)
The most arresting aspect of the Scottish Enlightenment is its conception of commercial society as a distinct and distinctive social formation. Christopher Berry explains why Enlightenment thinkers considered commercial society to be wealthier and freer than earlier forms, and charts the contemporary debates and tensions between Enlightenment thinkers that this idea raised. Key Features. The first book to focus on the Scottish Enlightenment's conception of commercial society, positioning it as the movement's core idea Analyses key works like Adam Smith's Wealth of Nations, David Hume's Essays and Treatises on Several Subjects and Adam Ferguson's Essay on the History of Civil Society Gives a full account by looking at the contemporary influence of lesser-known works such as Robert Wallace's Dissertation on Numbers of Mankind